Kegagalan Re-Eleksi Petahana dan Batas-Batas Incumbency advantage pada Pemilu Legislatif Kota Medan 2024 - Andika Syahputra Tj; Indra Fauzan; Tonny Pangihutan Situmorang (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study examines incumbency advantage in the 2024 Medan City Legislative Election, focusing on the low re-election rate of incumbent council members. Despite having access to publicly funded representative instruments, namely recess activities and local regulation socialization programs (sosper), only 19 of 50 members of the Medan City Council for the 2019-2024 term were re-elected. The study aims to identify factors behind incumbents’ electoral defeat and explain the relationship between recess and sosper activities and voter behavior. A descriptive qualitative approach was employed through in-depth interviews with seven informants, consisting of three re-elected incumbents, three unsuccessful incumbents, and one academic. The analysis was guided by David R. Mayhew’s incumbency advantage framework, including advertising, credit claiming, and position taking. The findings indicate that recess and sosper activities increased incumbents’ political visibility and strengthened ties with constituents. However, re-election outcomes were more strongly influenced by money politics, weak follow-up of public aspirations, internal party vote fragmentation, and voter polarization during the 2024 Presidential Election.